Efek Tepung Porang (Amorphophallus muelleri) yang Diberi Aluminium Sulfat Terhadap Fungsi Hati pada Tikus Winstar Diinduksi Asam Asetat - Elvina Artha Nainggolan; Agnes Pingkan Lamia; Verina Putri Gloria Nainggolan; Frans Erwin Nicolaas Wantania; dingse Pandiangan (PHARMACON, 2022)
This study aims to determine the side effects of porang flour solution added with Aluminum Sulfate on AST (Aspartate Aminotransferase) as an indicator of liver function in Wistar rats. This research was conducted in a laboratory with a completely randomized design with 3 replications. Treatment of porang flour solution was added with Aluminum Sulfate 3% (w/v) then added 3 g of porang flour. The rats before treatment were induced by gastric ulcers of rats with 12.5% acetic acid for 3 days. Treatment of porang flour solution was carried out for 21 days with a sonde. Parameters observed were movement, morphology, body weight (growth) and AST (U/L) on 7, 14 and 21 days after treatment. Data analysis was performed using Statistica 6 at a 95% confidence level. The results showed that porang flour treatment mice had a much lower body weight, were healthy, agile and moved a lot, indicating that porang flour plus aluminum sulfate can be developed as an alternative diet food. AST levels after 21 days of treatment with porang flour solution decreased. The recovery of Wistar rats induced by 12.5% acetic acid wounds for 3 days can be healed after 21 days given a 2 mL porang flour solution by sonde based on the results of morphological observations and decreased levels of AST.